Amanda Hogen: capstone - Hogen, Amanda, artist (Colorado State University. Libraries, 2015)
The artist's statement: As a graphic designer, I find my work to incorporate a traditional message of producing images and text that catches the audience's eye. At first, I didn't know where my work as a graphic designer was going. I then was fortunate enough to receive real world experience within advertisement, marketing, and social media. My completed work ranges throughout marketing, packaging design, rebranding, creative work, and social media. With each piece, I am able to produce clear information out to the audience through typography and imagery. As a designer, my desired work remains in the field of marketing.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design